2023
DOI: 10.1111/odi.14804
|View full text |Cite
|
Sign up to set email alerts
|

Non‐pharmacologic interventions for management of radiation‐induced dry mouth: A systematic review

Sukontha Khamdi,
Oranart Matangkasombut,
Aroonwan Lam‐Ubol

Abstract: ObjectivesRadiation‐induced dry mouth negatively impacts patients' oral health and quality of life. Currently, evidence‐based recommendation for non‐pharmacologic interventions is still lacking.This study aimed to systematically review clinical trials evaluating the efficacy of non‐pharmacologic interventions in cancer patients with radiation‐induced dry mouth.MethodsRandomized controlled trials from 2000 were searched from 4 databases, including MEDLINE, Cochrane, Embase via OVID, and SCOPUS, up to December 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
(187 reference statements)
0
3
0
Order By: Relevance
“…Notably, two of these studies indicated a high participation response rate, surpassing the required sample size 71 72. This fact, in conjunction with (1) inclusive eligibility criteria and (2) the observation that approximately 70% of irradiated patients with HNC suffer xerostomia and/or hyposalivation, increasing to 85% at 2 years after RT,3 18 73 suggests an adequate annual number of eligible patients (estimation of the prevalence in men/women in Spain 2020: 71 927 and 23 122, respectively) 74. Regarding recruitment rates, past studies have demonstrated rates between 73% and 76%,9 71 75 which indicates that a similar rate might be anticipated for the current trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, two of these studies indicated a high participation response rate, surpassing the required sample size 71 72. This fact, in conjunction with (1) inclusive eligibility criteria and (2) the observation that approximately 70% of irradiated patients with HNC suffer xerostomia and/or hyposalivation, increasing to 85% at 2 years after RT,3 18 73 suggests an adequate annual number of eligible patients (estimation of the prevalence in men/women in Spain 2020: 71 927 and 23 122, respectively) 74. Regarding recruitment rates, past studies have demonstrated rates between 73% and 76%,9 71 75 which indicates that a similar rate might be anticipated for the current trial.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of these methods include physical stimulation such as acupuncture and transcutaneous electrical nerve stimulation or artificial saliva products and hyperbaric oxygen therapy, all of which have limited supporting evidence. Even mesenchymal stem cell and gene transfer therapies have been proposed, although they have not yet been sufficiently investigated 15 18 19. Although the mechanics of photobiomodulation (PBM) are still not fully understood, the evidence suggests that this therapy can modulate the functional capacity of the glandular parenchyma, inducing salivary production 20.…”
Section: Introductionmentioning
confidence: 99%
“…Key characteristics of an effective saliva substitute include a suitable pH (~7), ion concentration (calcium and phosphate ions), and rheological properties that mimic natural saliva. A systematic review indicated that various commonly commercial products, such as Biotene Oral Balance (GSK, GSK Consumer Healthcare, Warren, NJ, USA), BioXtra Drymouth Systems (BioXtra, Herts, UK), and Oral Balance Gel (GSK, GSK Consumer Healthcare, Warren, NJ, USA), were effective in alleviating symptoms associated with xerostomia in patients suffering from radiation-induced dry mouth [ 13 ]. The saliva substitute was also expected to help promote suitable pH and ions that allow mineral precipitation.…”
Section: Introductionmentioning
confidence: 99%